Comparison Two of Different Technologies for Outdoor Positioning of Robotic Vehicles - Dvořák, Miroslav; Doležel, Petr (Springer Nature, 2019)
This paper aims to compare two different technologies, which can determine the exact position of a robotic vehicle. The first method uses wireless technology and is based on the measurement of the signal strength of the bluetooth beacons. Based on these values, you can calculate the distance from beacons. The second method uses laser light and measurement of the reflected pulses. Based on the reference points of reflection, we can determine the distance. Both methods then use 2D triangulation to determine the position of the robotic vehicle. The exact position of the bluetooth beacons or the reference points must be known for the calculation. The paper also describes experiments with a laser, and the conclusion provides an evaluation of both technologies.
Porovnání dvou přístupů k určování polohy autonomních vozidel
Keywords: bluetooth; iBeacon; laser; LiDAR; photodiode; RSSI; trilateration; bluetooth; iBeacon; laser; LiDAR; fotodioda; RSSI; trilaterace